2001
DOI: 10.1103/physrevb.63.125205
|View full text |Cite
|
Sign up to set email alerts
|

Stability of native defects in hexagonal and cubic boron nitride

Abstract: We investigate, through first-principles calculations, the stability and electronic structure of self-interstitials and vacancies in both hexagonal ͑graphite-like͒ and cubic boron nitride. We find that the self-interstitials N i and B i in hexagonal boron nitride (h-BN) have low formation energies, comparable to those of the vacancies V N and V B . For instance, we find that N i is the most stable defect in h-BN under N-rich and p-type conditions followed by the nitrogen vacancy. This is consistent with experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
124
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(133 citation statements)
references
References 23 publications
9
124
0
Order By: Relevance
“…In this respect, theoretical calculations yielded a very small distortion of the structure around a N vacancy after relaxation of the three B atoms around it in h-BN. 48 As we shall discuss later in more detail, only the intensity variation of peaks V and W is consistent with a perfect stacking of the basal planes parallel to the surface, while peaks X-Z slightly deviate from this geometry. In any case, a large spontaneous reorganization of the HOPBN structure is clearly observed by XANES owing to interaction with reactive oxygen in the air, either molecular or in the form of water vapor.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In this respect, theoretical calculations yielded a very small distortion of the structure around a N vacancy after relaxation of the three B atoms around it in h-BN. 48 As we shall discuss later in more detail, only the intensity variation of peaks V and W is consistent with a perfect stacking of the basal planes parallel to the surface, while peaks X-Z slightly deviate from this geometry. In any case, a large spontaneous reorganization of the HOPBN structure is clearly observed by XANES owing to interaction with reactive oxygen in the air, either molecular or in the form of water vapor.…”
Section: Resultsmentioning
confidence: 80%
“…Supporting this observation, theoretical calculations predict a higher formation energy for B monovacancies compared to N. 48,49 In contrast, high-resolution transmission electron microscopy (HRTEM) studies have reported recently the formation of point defects in h-BN single-layers, thinned down with a high-energy electron beam. 29,30,50,51 Strikingly, it seems that B vacancies are preferentially formed to N vacancies.…”
Section: Introductionmentioning
confidence: 89%
“…Given that the quantum emission from this defect is observed in monolayers and few-layer hBN materials, the defect is most likely intrinsic. The most likely candidates are a nitrogen vacancy (V N ), a boron vacancy (V B ) or an anti-site complex in which the nitrogen occupies the boron site and there is a missing atom at the nitrogen cite (N B V N ) 35,36 . We exclude the possibility of a di-vacancy as those have been shown to be highly unstable 37 .…”
mentioning
confidence: 99%
“…[19,24] The antisite defects are uniquely seen in h-BN and have long been investigated by experiments [43,44] and theory. [13,[45][46][47][48] However, the effects of antisite defects on the mechanical properties of h-BN remain unclear. By applying DFT calculations, we investigated the mechanical behaviour of two types of antisite defects in h-BN.…”
mentioning
confidence: 99%